2016
DOI: 10.1007/s00253-016-7827-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide signaling in yeast

Abstract: As a cellular signaling molecule, nitric oxide (NO) is widely conserved from microorganisms, such as bacteria, yeasts, and fungi, to higher eukaryotes including plants and mammals. NO is mainly produced by NO synthase (NOS) or nitrite reductase (NIR) activity. There are several NO detoxification systems, including NO dioxygenase (NOD) and S-nitrosoglutathione reductase (GSNOR). NO homeostasis based on the balance between NO synthesis and degradation is important for the regulation of its physiological function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 143 publications
0
22
0
1
Order By: Relevance
“…In that study and in ours, an increase in the NO level is closely correlated with the toxic effect of Pb on cells. In yeast, NO is generated mainly via NO synthase-like activity [48]. An increased level of NO in response to Pb exposure is mainly due to an increase in the expression of NO synthase-like genes [49][50].…”
Section: +mentioning
confidence: 99%
“…In that study and in ours, an increase in the NO level is closely correlated with the toxic effect of Pb on cells. In yeast, NO is generated mainly via NO synthase-like activity [48]. An increased level of NO in response to Pb exposure is mainly due to an increase in the expression of NO synthase-like genes [49][50].…”
Section: +mentioning
confidence: 99%
“…Nitric oxide (NO) is a diffusible free radical with a strong antimicrobial effect. NO is produced by nitric oxide synthase (NOS), which catalyzes the conversion of l ‐arginine into NO and l ‐citrulline 13 . In yeast, NOS‐like enzyme has been identified and its activity is regulated in a manner similar to NOS in mammalian cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive endogenous NO level can cause damage to the cell system as a result of the nitrosative stress development 15 . In particular, posttranslational modification of biomolecules induced by nitrosylation leads to specific pathways that inhibit cell growth or induce cell death 13 . Previous reports have shown that yeast cells treated with H 2 O 2 or menadione cause increased intracellular NO, thereby reducing cell viability 16 .…”
Section: Introductionmentioning
confidence: 99%
“…While little is known about NO synthesis in fungi, in mammals NO is synthesized by NO synthases (NOS isoforms), and NO functions as a signaling molecule and biomolecule modifier affecting various cellular processes. Imbalance in cellular NO levels leads to altered redox homeostasis, resulting in the production of reactive nitrogen species (RNS) responsible for nitrosative stress 8,9 . Type I flavohemoglobin constitutes the main enzyme deployed by microbes to counteract NO toxicity by converting it to inert nitrate, a source of nitrogen, via the NO-dioxygenation reaction 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Imbalance in cellular NO levels leads to altered redox homeostasis, resulting in the production of reactive nitrogen species (RNS) responsible for nitrosative stress 8,9 . Type I flavohemoglobin constitutes the main enzyme deployed by microbes to counteract NO toxicity by converting it to inert nitrate, a source of nitrogen, via the NO-dioxygenation reaction 8,9 . A type II flavohemoglobin has also been identified in Mycobacterium tuberculosis and other actinobacteria, but it lacks NO consuming activity and it utilizes D-lactate as an electron donor to mediate electron transfer 10,11 .…”
Section: Introductionmentioning
confidence: 99%